2018
DOI: 10.1093/infdis/jiy303
|View full text |Cite
|
Sign up to set email alerts
|

Postexposure Protective Efficacy of T-705 (Favipiravir) Against Sudan Virus Infection in Guinea Pigs

Abstract: Filoviruses such as Ebola virus (EBOV), Marburg virus (MARV), and Sudan virus (SUDV) cause deadly viral hemorrhagic fever in humans, with high case-fatality rates; however, no licensed therapeutic agent or vaccine has been clinically approved to treat or prevent infection. T-705 (favipiravir) is a novel antiviral drug that has been approved for the treatment of influenza in Japan. T-705 exhibits broad-spectrum antiviral activity against different viruses, including MARV and EBOV, and here, we are the first to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Alterations of some of these hematology and blood chemistry parameters were also found in guinea pigs [ 27 ], ferrets [ 61 , 62 ], IFNAR [ 43 ] and IFNAGR [ 39 ] mice on a C57BL/6J background, and in our study with STAT-1 KO mice. Consistent with previous observations in EBOV-infected IFNAGR KO mice [ 39 ] and human patients [ 63 ], we observed neutrophilia following SUDV challenge in our STAT-1 KO mice. Histopathology findings indicated that SUDV replicated in the liver and spleen of mice in our study, similar to NHPs [ 56 , 57 , 58 , 59 , 60 ], guinea pigs [ 27 , 64 ], and IFNAR KO mice [ 43 ], with features somewhat consistent with those described in the corresponding organs of EBOV-infected patients [ 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…Alterations of some of these hematology and blood chemistry parameters were also found in guinea pigs [ 27 ], ferrets [ 61 , 62 ], IFNAR [ 43 ] and IFNAGR [ 39 ] mice on a C57BL/6J background, and in our study with STAT-1 KO mice. Consistent with previous observations in EBOV-infected IFNAGR KO mice [ 39 ] and human patients [ 63 ], we observed neutrophilia following SUDV challenge in our STAT-1 KO mice. Histopathology findings indicated that SUDV replicated in the liver and spleen of mice in our study, similar to NHPs [ 56 , 57 , 58 , 59 , 60 ], guinea pigs [ 27 , 64 ], and IFNAR KO mice [ 43 ], with features somewhat consistent with those described in the corresponding organs of EBOV-infected patients [ 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is unclear what effect EBOV infection would have on the metabolic enzymes such as the P450’s in the guinea pig. To our knowledge, favipiravir has not previously been tested orally against EBOV in guinea pig (though it has demonstrated survival rates of 83-100% in Sudan virus-infected guinea pigs (35)), and in this study we now demonstrate efficacy on a par with what was observed in non-human primates (41, 42). In comparison, survival after pyronaridine (300 and 600 mg/kg) treatment was not significantly different from oral-administered favipiravir in the guinea pig model ((Log-rank (Mantel-Cox) test), suggesting a similar efficacy.…”
Section: Discussionsupporting
confidence: 55%
“…Favipiravir has been shown to protect guinea pigs from adapted Sudan Virus (35) however in our study it protected ∼44% of the animals against gpa-EBOV, with deaths starting on study day 6 and continuing until study day 14 (Fig. 3A).…”
Section: Resultsmentioning
confidence: 59%
“…To determine the usefulness of IFNAGR KO mice as a screening model for anti-filovirus countermeasures, we treated challenged mice with the antiviral Favipiravir. Indeed, Favipiravir was previously shown to be effective against wild-type EBOV in IFN-α/β receptor KO mouse models [ 45 , 46 , 47 ], mouse-adapted EBOV and MARV in respectively C57BL/6 or BALB/c mouse model [ 47 , 48 , 49 ], guinea pig-adapted SUDV in the guinea pig model [ 50 ] and wild-type EBOV or MARV in the NHP models [ 51 , 52 ]. Here, Favipiravir treatment was initiated 1 hour post-infection and infected mice were treated twice daily for 8 days.…”
Section: Resultsmentioning
confidence: 99%